If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 2 = (x + 7) + (x + -5) Reorder the terms: 2 + 6x = (x + 7) + (x + -5) Reorder the terms: 2 + 6x = (7 + x) + (x + -5) Remove parenthesis around (7 + x) 2 + 6x = 7 + x + (x + -5) Reorder the terms: 2 + 6x = 7 + x + (-5 + x) Remove parenthesis around (-5 + x) 2 + 6x = 7 + x + -5 + x Reorder the terms: 2 + 6x = 7 + -5 + x + x Combine like terms: 7 + -5 = 2 2 + 6x = 2 + x + x Combine like terms: x + x = 2x 2 + 6x = 2 + 2x Add '-2' to each side of the equation. 2 + -2 + 6x = 2 + -2 + 2x Combine like terms: 2 + -2 = 0 0 + 6x = 2 + -2 + 2x 6x = 2 + -2 + 2x Combine like terms: 2 + -2 = 0 6x = 0 + 2x 6x = 2x Solving 6x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 6x + -2x = 2x + -2x Combine like terms: 6x + -2x = 4x 4x = 2x + -2x Combine like terms: 2x + -2x = 0 4x = 0 Divide each side by '4'. x = 0 Simplifying x = 0
| 14-x=6 | | y=34/x-3/2+6/4 | | y=7/8x-7/4+20/4 | | 6d-1-3d=55+2d | | 11(x+4)-3x=4(2x+2)-10 | | 30=t-12 | | (4x^2+34x+40)/(x+7) | | 3d+4-(-2d)=5d+33 | | -14x+3(x-4)+7x=5x-12 | | 3d-4+(-2d)=5d+33 | | 2x+2(x-5)=3x-5 | | (3x/4)-(2x/5)=1 | | y-5=7/8x-7/8-2 | | 15x-8x=1 | | -2x-2=20-2 | | 12. 3(4x-1)=21 | | 5x+8=4-(7x-5) | | 5x+8=4-bracket(7x-5) | | 2x+6=7-(6x-4) | | 2(x+3)+2=10 | | x+3=x+7 | | 45-15=-15m | | 9y-7-5y=5y-6 | | 5*2-8=39x | | -1/1(x+1)=-4 | | 1/2(x+2)=1 | | -1/2x-5=-6 | | 4/x=7/4x+3 | | y+1=5/6(x-1) | | 65-4x=5x+15 | | y-1=5/6(x-1) | | 5-8x=77-36x |